2018
DOI: 10.1111/ppl.12730
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium promotes root nodulation through facilitation of carbohydrate allocation in soybean

Abstract: Magnesium (Mg) is an essential element for the growth of both plants and bacteria. Low availability of Mg in agriculture can limit crop productivity and quality. In addition to direct effects on plant growth, limited Mg supply may also impact biological dinitrogen (N ) fixation in nodules formed from symbiotic interactions between legumes and rhizobial bacteria. To date, the physiological mechanisms involved in Mg-dependent nodulation remains largely unknown. The objectives of this work were to assess how Mg s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 66 publications
1
22
1
Order By: Relevance
“…ARA in nodules was determined according to Peng et al (2018). Briefly, nodules were isolated with root segments left connected in order to prevent oxygen infiltration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ARA in nodules was determined according to Peng et al (2018). Briefly, nodules were isolated with root segments left connected in order to prevent oxygen infiltration.…”
Section: Methodsmentioning
confidence: 99%
“…Ureide concentrations were determined according to Peng et al (2018). In short, basal regions of soybean shoots (2 cm above the roots) were cut and xylem sap from roots was collected with a micropipette for 1 h. The concentration of ureides in xylem sap was determined using colorimetric analysis of glyoxylate derivatives using a spectrophotometer reading at the wavelength of 525 nm (UV‐1780; Shimadzu).…”
Section: Methodsmentioning
confidence: 99%
“…Suc was determined by the resorcinol method according to Peng et al (2018) using a Suc Assay Kit (Comin Biotechnology) as directed by the manufacturer. In brief, each sample was mixed with 1 mL of extract solution and heated at 80°C for 10 min.…”
Section: Suc Determinationmentioning
confidence: 99%
“…Nodulation was also reported to be regulated by K and Mg in the soil. Several studies demonstrated that a higher Mg concentration elicited a greater nodule number in soybean plants [64] and that a Mg deficit induced poor nodulation in alfalfa (Medicago sativa) plants [65]. It was also stated that nodulation was inhibited under a low K supply shortly before the rhizobium invaded the root hairs [35,66].…”
Section: Root Nodulation Response To Soil N K Mg and S Based On Bimentioning
confidence: 99%